Neuroprotective effect of Tozasertib in Streptozotocin-induced alzheimer’s mice model - Darshpreet Kaur; Amarjot Kaur Grewal; Suad Hamdan Almasoudi; Ahmad H Almehmadi; Bshra A. Alsfouk; Amit Kumar; Varinder Singh; Athanasios Alexiou; Marios Papadakis; Nermeen N. Welson; Thakur Gurjeet Singh; Gaber El-Saber Batiha (Scientific Reports)
Abstract Alzheimer’s disease (AD) is responsible for more than 80% of cases of dementia in senior individuals globally. In the current study, the role of modulation of the FGF1/PI3K/Akt pathway in the protective effect of tozasertib was evaluated. Experimental dementia was induced in mice by injecting streptozotocin (STZ) intracerebroventricularly. Various biochemical parameters for oxidative stress & lipid peroxidation (SOD, GSH, catalase, TBARS), neuroinflammation (MPO, IL-6, IL-1 β, TNF-α, NFκB), apoptotic markers (Bax, Bcl-2, Caspase-3), and memory parameters (AChE activity, β1–40 levels) were assessed. The behavioral parameters evaluated included the Morris Water Maze test and the step-down passive avoidance test. Histological changes were assessed using H&E staining. ICV STZ-induced AD resulted in increased oxidative stress, lipid peroxidation, neuroinflammation, apoptosis, and decreased learning and memory. The results showed that administration of tozasertib improved memory, decreased levels of oxidative stress, inflammatory parameters, and apoptotic markers, and improved histological parameters in a dose-dependent manner. Pre-administration of LY294002, a PI3K/Akt pathway inhibitor, partially reversed the protective effects of Tozasertib, suggesting possible involvement of this pathway. However, as the mechanism was inferred primarily through pharmacological antagonism, further studies including direct molecular assessments (e.g. p-Akt/t-Akt) are warranted to confirm the role of FGF1/PI3K/Akt signaling in Tozasertib’s action.